The Relationship Between Living Standards and Quality of Life: A Study of Urban Riverbank Settlements in Kotalama, Malang City - Fatahillah, Erland Raziqin; Surjono, Surjono; Hasyim, Abdul Wahid; Anggraeni, Mustika; Jasmine, Aurellia Parasti (Jurnal Pembangunan dan Alam Lestari, 2025)
Urbanization significantly transforms cities, introducing challenges affecting environmental sustainability and residents' quality of life. In urban riverbank settlements such as Kotalama, Malang City, these issues are compounded by inadequate planning, environmental degradation, and heightened disaster risks. This study investigates the relationship between living standards and quality of life in the urban riverbank settlements of Kotalama, Malang City. Using a quantitative approach, data were collected through secondary sources, including the Malang City Spatial Plan, and primary data via structured questionnaires distributed to 90 purposively sampled respondents. The analysis highlights the influence of environmental factors, housing quality, and social cohesion on residents' well-being. Regression analysis reveals a significant, albeit moderate, positive correlation between living standards and quality of life, underscoring the role of housing and infrastructure improvements in enhancing community well-being. While access to basic amenities such as water and electricity is adequate, disparities in housing quality and environmental conditions persist, affecting overall quality of life. The findings advocate for interdisciplinary strategies integrating urban planning, environmental sustainability, and participatory governance to address these challenges. This research contributes to urban sustainability discussions aligned with SDG Goal 11, promoting inclusive, resilient, and sustainable cities. Keywords: living standards, quality of life, urban riverbank, heightened disaster risk, environmental degradation